2004
DOI: 10.1016/j.vaccine.2003.11.066
|View full text |Cite
|
Sign up to set email alerts
|

A corn-based delivery system for animal vaccines: an oral transmissible gastroenteritis virus vaccine boosts lactogenic immunity in swine

Abstract: Recombinant plant expression systems offer a means to produce large quantities of selected antigens for subunit vaccines. Cereals are particularly well-suited expression vehicles since the expressed proteins can be stored at relatively high concentrations for extended periods of time without degradation and dry seed can be formulated into oral vaccines suitable for commercial applications. A subunit vaccine candidate directed against porcine transmissible gastroenteritis virus and expressed in corn seed has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
81
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(85 citation statements)
references
References 15 publications
1
81
0
2
Order By: Relevance
“…81 In the field of veterinary medicine, pigs fed with maize seeds containing the transmissible gastroenteritis virus (TGEV) spike protein were completely protected against the disease and also demonstrated lactoimmunity. 63,82,83 Rabbits were also protected against rabbit hemorrhagic disease virus A by feeding them a virus antigen expressed in pea seeds. 84 Passive immunization by mucosal application has also been attempted using plant-derived antibodies, including the HSV and S. mutans antibodies described above, and the anti-HIV microbicide being developed by the Pharma-Planta consortium.…”
Section: Discussionmentioning
confidence: 99%
“…81 In the field of veterinary medicine, pigs fed with maize seeds containing the transmissible gastroenteritis virus (TGEV) spike protein were completely protected against the disease and also demonstrated lactoimmunity. 63,82,83 Rabbits were also protected against rabbit hemorrhagic disease virus A by feeding them a virus antigen expressed in pea seeds. 84 Passive immunization by mucosal application has also been attempted using plant-derived antibodies, including the HSV and S. mutans antibodies described above, and the anti-HIV microbicide being developed by the Pharma-Planta consortium.…”
Section: Discussionmentioning
confidence: 99%
“…[22] It may be useful to screen for these sites and remove them by modifying the gene of interest to increase gene expression. The level of amino acid can also be a limiting factor in the expression of particular proteins, it is necessary to alter amino acid synthesis pathways for the expression of some particular proteins.…”
Section: (D) Stable Transformation Of a Plant Species That Is Grown Hmentioning
confidence: 99%
“…Plants can be grown economically in large quantities under the sunlight as the energy source, and indigenous agricultural technologies can be used for vaccine harvest [19]. The edible vaccines should be particularly suited for use in farm animals destined for meat markets, because the carcass quality may be compromised by repeated injections; therefore, in such cases, oral vaccines can prove to be useful since that kind of problems can be overcome [9].…”
mentioning
confidence: 99%
“…Other investigators reported that when swine transmissible gastroenteritis virus (TGEV) antigen was expressed in transgenic maize, it was shown to be accumulated at levels of 40 g/g fresh weight and the transgenic maize grains was shown to be efficacious in partially preventing viral infection after the host animals, i.e., pigs, were fed with them [8,9,18]. Another study has reported that transgenic rice seed containing approximately 60 g/grain of T cell epitope peptide composed of seven major human T cell epitopes derived from the Japanese cedar pollen allergen Cry j 1 and Cry j 2 was efficacious in preventing allergic responses in an experimental animal model [22].…”
mentioning
confidence: 99%